Effect of a previous high intensity running exercise on isokinetic muscular strength in individuals with different training backgrounds - Denadai, Benedito Sergio [UNESP]; Corvino, Rogerio Bulhoes [UNESP]; Greco, Camila Coelho [UNESP] (IOS Press, 2010)
The objective of this study was to compare the effects of high intensity running exercise on the strength of the knee extensors at concentric and eccentric conditions in individuals with different training background. Sixteen physically active (SED), 11 endurance-trained (ET) and 7 strength-trained (ST) subjects volunteered to participate in the study. Initially each subject performed, on different days, one familiarization session on an isokinetic dynamometer and an incremental treadmill test to volitional exhaustion to determine the velocity at the onset of blood lactate accumulation (OBLA). The subjects then returned to the laboratory on two experimental sessions, separated by at least five days, to perform maximal isokinetic eccentric (E) and concentric (C) contractions of the quadriceps at 180 degrees/s. One session was performed after a standardized warm-up period (5 min at 50% VO(2)max) and the other session was performed after a continuous running at 95% OBLA. The duration of this session was estimated to a caloric expenditure around 500 Kcal. Following this high intensity exercise there was a significant reduction in the peak torque in E in all groups. The percent strength loss in E following the running exercise was statistically higher in ST (16.5%) when compared to SED (6.5%) and ET (7.2%). We thus conclude that the reduction in isokinetic peak torque of the knee extensors after a session of high intensity running exercise at 95% OBLA depends on the contraction type and training background.
Keywords: Concentric; eccentric; aerobic exercise; fatigue